Kamus Bali-Indonesia Bidang Istilah Tata Rias Pengantin Bali - Asmara, I Wayan Giri; Ariana, I Putu; Sulibra, I Ketut Ngurah (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The research entitled “Balinese–Indonesian Dictionary of Terms in Balinese Bridal Makeup” aims to describe the forms of terminology used in bridal makeup practices. The theoretical framework applied in this study is lexicology, supported by structural linguistics. The data collection stage employed introspection, observation, and interview methods, followed by advanced techniques such as recording and note-taking. For data analysis, two methods were applied: the identity method and the distributional method. The identity method was elaborated with the basic technique of determinant element division (PUP) and the translational identity method, whose determinant tools are derived from another language, accompanied by comparative techniques HBS (equating comparison) and HBSP (equating comparison of core elements). The distributional method was used to explain word classes and microstructural analysis of language, followed by techniques such as immediate constituent analysis (BUL), deletion, substitution, and insertion. The presentation of data analysis results employed both formal and informal methods with deductive techniques. The findings of this study reveal 245 Balinese terms in the field of bridal makeup, consisting of root words, derived words, and phrases.